Evaluation of the Medicare-DoD Subvention Demonstration Final Report - Farley, Donna O. (RAND Corporation, 2003)
The Medicare-Department of Defense (DoD) Subvention Demonstration tested Senior Prime as a managed care approach for enhancing access to affordable health care for Medicare-eligible DoD beneficiaries. The authors found that while Senior Prime achieved solid beneficiary participation and satisfaction, it also raised a difficult set of challenges involved in applying managed care to the DoD health care system.